Bids, Proposals and Tenders : Succeeding with Effective Writing - Nickson, David (British Computer Society, 2012)
Annotation This book is a must-have for anyone producing bids and proposals ranging from short covering letters through to tenders for major corporate or government procurement. Sales, marketing, project and technical staff will all benefit from reading the book and keeping a copy on their shelves for reference. It is also useful for business students at all levels. Contents include: The Art of Proposal Writing; The Proposal Lifecycle; Presentation and Format; Corporate and Client Culture.
Keywords: Proposal writing in business.; Letting of contracts.; elektronické knihy; electronic books